(The Effect of Variety and Soaking Duration on Brine to the Quality of Preserved Salak (Salacca Edulis, Reinw) - Sutrisniati, Dwi; -, Sumarsi; Kusdini, Nenden; Sutisna Achyadi, Nana (Balai Besar Industri Agro, 1998)
A study to find the best condition in producing preserved salak (snake fruit) has been conduced. The variables used are type of salak and duration of soaking in brine.The result showed that 3 days soaking in 10% brine for Cibodas type gave a good preserved salak. The product was well accepted by the panelists. The analysis on the best preserved salak gave the following result: moisture content 11.99%, sucrose 42.20%, vitamin C 2.18 mg/100 g whiteness 44.50% and firmness 2.15 mm/g.